30 years of advances in functionalization of carbon nanomaterials for biomedical applications: a practical review. Issue 1 (19th December 2016) - Bardhan, Neelkanth M.
Abstract: Abstract : Carbon-based nanomaterials (CANOMATs), including fullerenes, carbon nanotubes, graphene, and their derivatives, are widely considered to be the next-generation materials for a broad range of biomedical applications, owing to their unique opto-electronic, chemical, and mechanical properties. However, for bio-applications, CANOMATs need to be surface-functionalized, to render them passive, non-toxic, and water-soluble. Here, we review the current state-of-the-art in the methods of functionalization of CANOMATs. In contrast to other Reviews, we present an objective analysis of the various approaches reported in the literature, using metrics such as the agent of functionalization, number of steps, and time required, the need for special instruments, effect on properties, scalability, reproducibility, and applications. Our Review offers a way for researchers to make a rational selection of the process of functionalization to best suit their desired application. This opens up new opportunities for developing targeted functionalization strategies, based on the need to excel at the above metrics.